Antonio Boggeri. Considerazioni su un protagonista della grafica italiana - Camilla Chiappini (Ricerche di S/Confine, 2012)
Antonio Boggeri is often remembered in the history of graphics only as the Studio Boggeri’s holder. Indeed he is one of the most important figures of Italian advertising graphics and this not for the works he materially made in this field but for his centrality in the Studio he created: in fact he was the unifying element in it among artists of different personality and sensibility.This article does not pretend to explain in a comprehensive manner his importance but it wants to represent a starting point in a research that reconsiders all round Boggeri. Not only, therefore, for his central role in the Studio, but even for his important contribution as a writer and as a photographer, compensating, in part, the lack of works that fully analyze his figure.